Establishment of horse blood-brain barrier model for the study of drug delivery to the brain - Gupta, Gaurav (2025)
The lack of a benchmark standard in vitro model of blood-brain barrier (BBB) is the principal reason behind high failure rates of central nervous system drugs in clinical trials during their development phase. In the last few decades, in vitro models of BBB have been developed using brain endothelial cells from various species like rat, mice, pig, and cattle However, no in vitro BBB model till date has been developed using horse brain endothelial cells. Hence, the main aim of this study was to establish an in vitro primary horse brain endothelial cell (HBEC) transwell model of BBB for determining the how much drugs are transported and handled by the BBB by measuring various pharmacokinetic parameters.